Assessment of Water Quality in Kuntaur, Central River Region, The Gambia - Oladele Oyelakin; Mustapha Conteh; Osaro Iyekowa; Adjivon Anthony; Mandalena Mendy; Chukwudozie Cyril Ntomchukwu (The Journal of Pure and Applied Chemistry Research, 2020)
The study deals with twelve water quality parameters on twenty-four sampling locations in Kuntaur. Samples were collected from the both surface water and groundwater.  Twelve parameters were: temperature, pH, conductivity, acidity, alkalinity, total dissolved solids, turbidity, iron, nitrite, nitrate, sulphate and phosphorus (orthophosphate). Nearly all the measured parameters fell within the standard reference of the various parameters. The standards were: National Environment Agency, NEA, (The Gambia), World Health Organization, WHO and European Union, EU, Standards.